(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Multiferroic materials, possessing both ferroelectric and ferromagnetic properties, have garnered immense interest in the realm of condensed matter physics and advanced materials science due to their remarkable potential for multifunctional applications.